2005
DOI: 10.1086/430931
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Production Is Profoundly and Transiently Impaired in Primary HIV‐1 Infection

Abstract: These data underline the potential for early antiretroviral treatment and IFN- alpha treatment to enhance viral control in a larger proportion of patients during the critical stage of primary infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
112
3
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 52 publications
14
112
3
1
Order By: Relevance
“…pDC function may also be altered by HCV [35]. Infection with HIV also reduces pDC function, both in chronic and primary HIV infection although the decrease in function may be mostly due to reduced pDC numbers [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…pDC function may also be altered by HCV [35]. Infection with HIV also reduces pDC function, both in chronic and primary HIV infection although the decrease in function may be mostly due to reduced pDC numbers [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…These effects can be partially reversed by antiretroviral therapy (14). Additionally, pDCs isolated from individuals acutely infected with HIV exhibit an impaired ability to secrete type 1 IFNs (15,16). The underlying cause(s) of these alterations in pDC numbers and activity, as a result of HIV infection, are unknown.…”
mentioning
confidence: 99%
“…During retroviral infections, such as HIV, SIV, or Friend retro virus (FV), the type I IFN response is quite weak. It was shown that during primary HIV infection, type I IFNs are barely detectable because of a decrease of plasmacytoid DCs (26), the most important IFN-a producers. This was also observed in chronic HIV infections (27).…”
mentioning
confidence: 99%